Uranium isotopes in groundwater occurring at Amazonas State, Brazil - Silva, Marcio Luiz da; Bonotto, Daniel Marcos [UNESP] (Elsevier B.V., 2015)
This paper reports the behavior of the dissolved U-isotopes U-238 and U-234 in groundwater providing from 15 cities in Amazonas State, Brazil. The isotope dilution technique accompanied by alpha spectrometry were utilized for acquiring the U content and U-234/U-238 activity ratio (AR) data, 0.01-1.4 mu g L-1 and 1.0-3.5, respectively. These results suggest that the water is circulating in a reducing environment and leaching strata containing minerals with low uranium concentration. A tendency to increasing ARs values following the groundwater flow direction is identified in Manaus city. The AR also increases according to the SW-NE directions: Uarini -> Tefe; Manacapuru -> Manaus; Presidente Figueiredo -> Sao Sebastiao do Uatuma; and Boa Vista do Ramos -> Parintins. Such trends are possibly related to several factors, among them the increasing acid character of the waters. The waters analyzed are used for human consumption and the highest dissolved U content is much lower than the maximum established by the World Health Organization. Therefore, in view of this radiological parameter they can be used for drinking purposes.
Keywords: Groundwater; Tube wells; Dissolved uranium; U-234/U-238 activity ratio; Amazon area